Deskripsi Objek Wisata Kawasan Pesisir Kali Biru - Sri Nurdiana; La Ode Amaluddin; La Harudu (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2023)
Problems that often arise in tourist objects, namely inadequate and supportive infrastructure facilities. Infrastructure that is often a concern is road access to tourist attractions, availability of parking lots, landfills to public toilets. The research objectives were to describe: 1) the condition of the Kali Biru tourist attraction; and 2) the tourism potential of Kali Biru. The method used in this research is descriptive qualitative method with 25 respondents. The data in this study were collected through observation, interviews and documentation. The results of the study show that: 1) the Kali Biru tourist attraction has tourism potential which can be seen in terms of adventurer potential which includes accessibility and infrastructure contained in the Kali Biru tourist attraction. These potentials vary from those that are still maintained to those that are not maintained so that more attention is needed, repairs and improvements in a better direction; 2) The beauty of the sea water at the location of the tourist attraction is also a potential main natural attraction in Kali Biru. The clear blue and clean sea, the presence of coral reefs, geomorphological appearance in the form of views around directly facing mangroves and there is a sunrise, can spoil the eyes of tourists to visit again.